Evaluation of Electrode Deposition and Corrosiveness in HHO Generators: A Comparative Study Between Theoretical Predictions and Experimental Results - Bernardus Crisanto Putra Mbulu; Antonius Prisma Jalu Permana; Donysius Dwi Hercahyo (Proceeding of the International Conference on Mathematical Sciences, Natural Sciences, and Computing, 2024)
Abstract: Renewable Energi have been goverment concern in Indonesia since 2014. HHO generator is one of some machine to generate hydrogen fuel using electrolysis process. In this research, the discussion will focus on the comparison between theoretical predictions and experimental results, about the causes of precipitation and corrosion of electrodes made of stainless steel produced from HHO generators, especially when using a mixture of KOH and NaCl electrolytes. The results, show the precipitate produced by the KOH solution is less compared to the NaCl solution. Meanwhile, the chlorine (Cl⁻) content of NaCl which is initially corrosive is not always present because it is formed into Cl₂ in the form of a gas, so the subsequent precipitation and corrosiveness depend on the element hydroxide (OH⁻) from H₂O dissociation.